Historical aspects of audit development as a type of economic activity - V.V. Savitskyi; V.M. Parshakov (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
In the course of the research, the scientific literature was analyzed in terms of historical aspects of audit development. The analysis of scientific papers shows that there is no unified approach to audit periodization; this situation has developed due to a combination of objective reasons: the theory underlying the research, the object of research, methods and objectives of the research. Our research was based on the study of historical aspects of business audit in the following order: the origins of audit as an institution of financial control; the formation and evolution of audit in Ukraine (as part of the Russian Empire and the Soviet Union); the emergence of audit and the development of audit in its modern sense; modern trends in audit in the world. During the study it was found that the modern state of audit as an independent financial control and as commercial activity is determined by the external environment of the following aspects: the specific socio-economic relations from the position of the subject of the audit as a tool for independent financial control, specific development management science from the position of introduction of auditing as a tool of the relationship between the management units, development of audit as consulting from a position of auditing as a business. The article investigates institutional support (a set of state, professional and public institutions whose main functions are the regulation of audit and auditing activities) of audit framework of Western European countries.